The legacy of 9/11 views from North America - Anderson, Greg 1969- (McGill-Queen’s University Press, 2023)
"While 9/11 was understood at the time as a world-changing event in international relations, its uneven aftermath and the long-term effects for North America could not have been predicted. Twenty years later, The Legacy of 9/11 explores the political, economic, security and defence, and trade and border implications of the event. Written by a team of North American experts across many fields, the book foregrounds the fallout of 9/11 in Mexico and Canada as opposed to the more commonly discussed impact on the United States. Looking at the event and its aftermath through four lenses--ideas about North America; border, trade, and economics; security and society; and defence--contributors analyze the complex legacy of 9/11. Rather than serving as a catalyst to create an integrated, trilateral continent, 9/11 entrenched the North America we have today: three separate states with emphasis on two very different borders. From a reconsideration of internationalism, a rise in populism, and a shift in migration patterns to the interventions in Afghanistan and Iraq, The Legacy of 9/11 uncovers how successive North American governments reacted in surprising ways to the world-altering attack."--
Keywords: Geschichte; Handel; Sicherheitspolitik; Grenzschutz; Auswirkung; Gesellschaftsleben; Elfter September; Mexiko; Nordamerika; September 11 Terrorist Attacks, 2001 / Influence; Canada / Economic policy / 21st century; Mexico / Economic policy / 21st century; National security / Canada; National security / Mexico; Canada / Defenses; Mexico / Defenses; POLITICAL SCIENCE / Security (National & International); Economic policy; Influence (Literary, artistic, etc.); Military readiness; National security; Canada; Mexico; 2000-2099; Aufsatzsammlung